2001
DOI: 10.1128/jvi.75.11.5335-5342.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complete In Vitro Assembly of the Reovirus Outer Capsid Produces Highly Infectious Particles Suitable for Genetic Studies of the Receptor-Binding Protein

Abstract: Mammalian reoviruses, prototype members of the Reoviridae family of nonenveloped double-stranded RNA viruses, use at least three proteins-1, 1, and 3-to enter host cells. 1, a major determinant of cell tropism, mediates viral attachment to cellular receptors. Studies of 1 functions in reovirus entry have been restricted by the lack of methodologies to produce infectious virions containing engineered mutations in viral proteins. To mitigate this problem, we produced virion-like particles by "recoating" genome-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 50 publications
(40 reference statements)
4
62
0
Order By: Relevance
“…(Virions and ISVPs of some reovirus strains can bind to RBCs via 1 attachment to cell-surface sialic acid; however, particles of the strain used in this study do not bind in this way to bovine RBCs.) Similar results with recoated virus-like particles lacking 1 (32) confirmed that RG association is not 1 dependent (data not shown). In addition, viral cores lacking all outer-capsid proteins sedimented to the bottom, confirming that an outer-capsid protein is required for RG association (data not shown).…”
Section: Isvp* Particles and Released Component 1n Are Recruited To Rbcsupporting
confidence: 75%
See 2 more Smart Citations
“…(Virions and ISVPs of some reovirus strains can bind to RBCs via 1 attachment to cell-surface sialic acid; however, particles of the strain used in this study do not bind in this way to bovine RBCs.) Similar results with recoated virus-like particles lacking 1 (32) confirmed that RG association is not 1 dependent (data not shown). In addition, viral cores lacking all outer-capsid proteins sedimented to the bottom, confirming that an outer-capsid protein is required for RG association (data not shown).…”
Section: Isvp* Particles and Released Component 1n Are Recruited To Rbcsupporting
confidence: 75%
“…Digestion was stopped by addition of 300 g͞ml soybean trypsin inhibitor (Sigma) and incubation on ice for at least 15 min. T1L cores and cores recoated with WT T1L 1 and 3 were made as described (32), except that virions were digested for 3-4 h, cores were purified by banding on CsCl step gradients (1.30-1.53 g͞cm 3 ), and cores were recoated by incubating with insect cell lysates for Ϸ4 h, followed by banding on CsCl step gradients (1.30-1.45 g͞cm 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because particle-free 1(N42A) can disrupt liposomes (Fig. 2B), we investigated the disruption activity of cores recoated with 1(N42A) (12,13). Previous work has shown that recoating with 1(N42A) yields correctly assembled virion-like particles, which undergo normal disassembly steps, including the structural rearrangement of 1 to a protease-sensitive form (42).…”
Section: Resultsmentioning
confidence: 99%
“…3D) In contrast to the flap-like structure on the orthoreovirus λ2 or the aquareovirus VP1, the spike-like complex of CPV sits on the turret substituting for the flap-like structure of orthoreoviruses or aquareoviruses. The turret of orthoreoviruses and aquareoviruses can adopt both closed and open states (8,20,(33)(34)(35). The biological mechanism behind the open/closed state of the turret is still elusive.…”
mentioning
confidence: 99%